The Symposium of history and banking civilization „Cristian Popişteanu”, Edition XXII, Bucharest, May 7, 2014 (Confluenţe Bibliologice, 2014)
The symposium was devoted to Cristian Popişteanu, a journalist and a historian, being paid tribute to those who knew him and worked with him. The views expressed by the word were under the sign of «round table» moderated by Cristian Paunescu. The speakers emphasized the complexity of the character of Cristian Popişteanu which he left many scientiﬁc papers and memories.  Reverential volume written by the Cultural Foundation Magazin Istoric has published more than 100 memories, dedications and signatures of national and international personalities.
Keywords: Romanian personalities